Anxiolytic- and antidepressant-like effects of Bacillus coagulans Unique IS-2 mediate via reshaping of microbiome gut-brain axis in rats. (February 2023) - Satti, Srilakshmi; Palepu, Mani Surya Kumar; Singh, Aditya A.; Jaiswal, Yash; Dash, Surya Prakash; Gajula, Siva Nageswara Rao; Chaganti, Sowmya; Samanthula, Gananadhamu; Sonti, Rajesh; Dandekar, Manoj P.
Abstract: Background: Due to the rising cases of treatment-refractory affective disorders, the discovery of newer therapeutic approaches is needed. In recent times, probiotics have garnered notable attention in managing stress-related disorders. Herein, we examined the effect of Bacillus coagulans Unique IS-2® probiotic on anxiety- and depression-like phenotypes employing maternal separation (MS) and chronic-unpredictable mild stress (CUMS) model in rats. Methods: Both male and female Sprague-Dawley rats were subjected to MS + CUMS. Probiotic treatment was provided for 6 weeks via drinking water. Anxiety- and depression-like phenotypes were assessed using sucrose-preference test (SPT), forced-swimming test (FST), elevated-plus maze test (EPM), and open-field test (OFT). Blood, brain, intestine, and fecal samples were obtained for biochemical and molecular studies. Results: Stress-exposed rats drank less sucrose solution, showed increased passivity, and explored less in open-arms in SPT, FST, and EPM, respectively. These stress-generated neurobehavioral aberrations were alleviated by 6-week of Bacillus coagulans Unique IS-2 treatment. The overall locomotor activity in OFT remained unchanged. The decreased levels of BDNF and serotonin and increased levels of C-reactive protein, TNF-α, IL-1β, and dopamine, in the hippocampus and/or frontal cortex of stress-exposed rats were reversed following probiotic treatment. Administration of probiotic also restored the systemic levels of L-tryptophan, L-kynurenine, kynurenic-acid, and 3-hydroxyanthranilic acid, villi/crypt ratio, goblet-cell count, Firmicutes to Bacteroides ratio, and levels of acetate, propionate, and butyrate in fecal samples. These results indicate remodeling of the microbiome gut-brain axis in Bacillus coagulans Unique IS-2 recipient rats. However, protein levels of doublecortin, GFAP, and zona occludens in the hippocampus and occludin-immunoreactivity in the intestine remained unchanged. No prominent sex-specific changes were noted. Conclusion: Anxiolytic- and antidepressant-like effects of Bacillus coagulans Unique IS-2 in MS + CUMS rat model may be mediated via reshaping the microbiome gut-brain axis. Graphical abstract: Image 1 Highlights: Treatment-refractory cases of affective disorders are rising worldwide. Ingestion of probiotics produces positive effects on stress-related disorders. Bacillus coagulans Unique IS-2 modulated the key neurotransmitters and cytokines. Bacillus coagulans Unique IS-2 normalized the levels of L-tryptophan metabolites. Bacillus coagulans Unique IS-2 attenuated anxiety- and depressive-like phenotypes.